KIRAB PUSAKA KERATON KASUNANAN SURAKARTA DALAM PERSPEKTIF ETIKA DEONTOLOGI IMMANUEL KANT - John Abraham Ziswan Suryosumunar; Fuad Noorzeha (Sanjiwani: Jurnal Filsafat, 2022)
The Javanese are one of the largest ethnic groups in Indonesia, whose presence spreads not only throughout Indonesia, but also dominates the population in several areas in other countries, such as in Suriname and New Caledonia. Javanese ethnic culture is basically centralized from the past kingdoms which are still standing today, namely Surakarta and Yogyakarta. The Javanese cultural character that upholds social and spiritual harmony is one of the factors why this ethnic group is easy to adapt to local communities from various regions. It is interesting for the writer to explore the practice of Javanese traditions that still survive to this day which is a symbol of the harmony of the macrocosm and microcosm, one of which is the kirab pusaka from the Kasunanan Surakarta Palace. The author, using the method of philosophical hermeneutics, tries to analyze the tradition in the Deontology ethical perspective of Immanuel Kant. This analysis can be useful for understanding the correlation of the implementation of the kirab pusaka with the basic obligations held by the indigenous people of the Surakarta Kasunanan Palace in carrying out the kirab pusaka tradition.